Analysis of Sportfishing Tourism Potential A Phenomenological Study in Jatigede Reservoir - Gilang Nurfaizal; Rizal Ahmad Fauzi; Adang Sudrajat (Universitas Tadulako, 2026)
This study aims to analyze the potential for fisheries tourism development in the Jatigede Reservoir, Sumedang Regency, using a qualitative descriptive research method with an analytical framework of Marketability, Sustainability, Participation, and Disaster Mitigation (MSP-DM). Jatigede has a unique submerged forest ecosystem, unlike other dams, which serves as a habitat for large predatory fish such as Hampala and Channa, creating specific technical challenges for the national sportfishing community. Data collection was conducted through participant observation, document review, and in-depth interviews with managers, fishing communities, local communities, and the Indonesian Fishermen's Association (APRI). The findings reveal a paradox between economic exploitation and conservation; where massive digital promotion has made Jatigede a